A Robust Mutual Authentication Protocol for Wireless Sensor Networks - Chen, Tien‐Ho; Shih, Wei‐Kuan (ETRI journal, 2010)
Authentication is an important service in wireless sensor networks (WSNs) for an unattended environment. Recently, Das proposed a hash‐based authentication protocol for WSNs, which provides more security against the masquerade, stolen‐verifier, replay, and guessing attacks and avoids the threat which comes with having many logged‐in users with the same login‐id. In this paper, we point out one security weakness of Das' protocol in mutual authentication for WSN's preservation between users, gateway‐node, and sensor nodes. To remedy the problem, this paper provides a secrecy improvement over Das' protocol to ensure that a legal user can exercise a WSN in an insecure environment. Furthermore, by presenting the comparisons of security, computation and communication costs, and performances with the related protocols, the proposed protocol is shown to be suitable for higher security WSNs.